2016
DOI: 10.1002/dc.23522
|View full text |Cite
|
Sign up to set email alerts
|

The utility of cellient cell blocks in low‐cellularity thyroid fine needle aspiration biopsies

Abstract: The use of CBs in low-cellularity thyroid FNAs has not been well described. In this study, we found that the contribution of CBs in this setting varied by TBSRTC category. Specifically, the samples that benefited most were initially non-diagnostic specimens and select cases of AUS/FLUS, while low-cellularity benign samples gained very little additional information. Diagn. Cytopathol. 2016;44:737-741. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…The majority of our cases showed cellular cell block material with only a few with borderline adequate material. Our findings are essentially in agreement with diagnostic utility of cell block material in previous reported studies . We have also noticed that presence of adequate material on pap stained slides along with the cellular material on cell block enhance the diagnostic details and complement the characterization in to a definitive TBSRTC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The majority of our cases showed cellular cell block material with only a few with borderline adequate material. Our findings are essentially in agreement with diagnostic utility of cell block material in previous reported studies . We have also noticed that presence of adequate material on pap stained slides along with the cellular material on cell block enhance the diagnostic details and complement the characterization in to a definitive TBSRTC.…”
Section: Discussionsupporting
confidence: 92%
“…Cristo et al in a study of 358 patients compared cytology and combined cytology cell block nondiagnostic rates and found 17.1% vs 4.3%, respectively . Others have also found that the use of cell block material yields diagnostic material in 31% of nondiagnostic ThinPrep . Similarly, we compared nondiagnostic rates between cytology (without cell block) and combined cytology and cell block and found comparable values, 16.4% vs 9.3%, respectively.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The material remaining after the slide preparation has been completed can be used for the application of immunocytochemistry on cell block material as well as for other ancillary techniques. The application of the cell block technique on thyroid FNA material has been described in the literature as having very good results, particularly in cases of unsatisfactory or intermediate cytology [15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Both alcohol and formalin fixation are possible with morphology and cellularity seem to be superior to traditional CB techniques . For thyroid specimens, automated methods are preferable in the case of nondiagnostic and atypia of undetermined significance/follicular lesion of undetermined significance results, but yield little additional information in the case of low‐cellularity specimens . Importantly, immunocytochemical protocols for both manual and automated methods should be optimised and adapted for formalin or alcohol‐fixed specimens …”
Section: Cell Block (Cb) Preparationmentioning
confidence: 99%